COUNTER DISCOURSE ON MENTAL HEALTH ISSUES IN GENERATION Z ON TWITTER - Loho, Pieter Wilson; Isnaini, Muhamad (RADJA PUBLIKA, 2023)
This research is motivated by the massive issue of mental health on social media, especially Twitter. Generation Z is the party most stigmatized for mental health issues. This research seeks to answer how discourse develops regarding mental health issues among generation Z on Twitter. This research uses a qualitative approach with virtual ethnographic methods. Generation Z netizens' conversations on Twitter were recorded using cloud-based software Netlytic. The research results show the diversity of discourse on mental health issues. This discourse shows that generation Z displays a counter strategy, namely leaving the dominant discourse on mental health. This counter-discourse arose because so far mental health has always been associated with dictions such as depression, anxiety, stress, and even suicide. To find a solution to this threatening diction, they create a new discursive strategy by saying that mental health is nothing more than a matter of religiosity, espoused values, or seeking professional help.